2011
DOI: 10.3354/meps09194
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the effect of vertical mixing on bottle incubations for determining in situ phytoplankton dynamics. II. Primary production

Abstract: C) during the incubation period (typically 24 h). One of the main concerns with using fixed-depth bottle incubations is whether stranding samples at fixed depths biases the measured CO 2 fixation relative to the 'true' in situ mixed conditions. Here we employ an individual based turbulence and photosynthesis model, which also accounts for photoacclimation and -inhibition, to examine whether the in vitro productivity estimates obtained from fixed-depth incubations are representative of the in situ productivity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 32 publications
1
15
0
Order By: Relevance
“…8). Moore et al (2006) suggested high E k indicates acclimation to irradiance above the average growth irradiance, but there has been some debate regarding the depth to which cells in well-mixed regimes are acclimated Moore et al 2006;Ross et al 2011). Our results indicate that in dynamic environments, optimal resource allocation to light harvesting and corresponding Chl : C both decrease with increasing ILD (Figs.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…8). Moore et al (2006) suggested high E k indicates acclimation to irradiance above the average growth irradiance, but there has been some debate regarding the depth to which cells in well-mixed regimes are acclimated Moore et al 2006;Ross et al 2011). Our results indicate that in dynamic environments, optimal resource allocation to light harvesting and corresponding Chl : C both decrease with increasing ILD (Figs.…”
Section: Discussionsupporting
confidence: 56%
“…Resources allocated to carbon fixation influence the capacity of the cell to accumulate energy and carbon reserves in the form of lipid and carbohydrate (Ross and Geider 2009). Energy fixed in reserve polymers can be used to fuel growth in low light or darkness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the spectral dependence of underwater light attenuation, an increase in total irradiance caused by shallow mixing will be accompanied by increasing proportions of shortwave UVR. The dynamic nature of light exposure is still poorly resolved in experimental settings, and its biogeochemical consequences are not well understood (Bertoni et al 2011;Ross et al 2011). Our experimental setup, while not totally realistic, provided a first approximation towards understanding the photobiological bases of some DMS production pathways.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that all experiments took place in soft wind conditions, and the relatively high values of the buoyancy (Brunt-Väisälä) frequency within the UML suggest that it was not mixing actively at the time of the CTD casts (Table 1). If we assume that vertical diffusivity (K z ) in the UML interior was in the range 10 −2 -10 −4 m 2 s −1 (Denman and Gargett, 1983;Ross et al, 2011b), it would take ca. 0.25 to 100 h for a population of particles released at a single depth to diffuse across one optical depth in the UML depending on the wavelengths and MLD considered (Gallegos and Platt, 1985).…”
Section: Oceanographic Settingsmentioning
confidence: 99%